Analysis of Air Quality Changes at Punagaya Steam Power Plant based on Total Suspended Particulate (TSP) parameters - Hildayani; Muhammad Nadir (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Punagaya Steam Power Plant (PLTU) is one of Power Plant in the Southern Sulawesi system. Apart from having a positive impact, PLTU can have a negative impact on the environment due to burning coal as fuel. One of the dangerous air pollutants that is often found is Total Suspended Particulate or TSP. This research aims to determine changes in TSP, PM2.5 and PM10 concentration values at the Punagaya PLTU location from May 2022 and June 2023. The method for measuring concentrations of TSP, PM10, and PM2.5 air particles uses High Volume Air Sampler (HVAS) equipment with gravimetric method. Based on the analysis results of air particles around the Punagaya PLTU, the concentrations of TSP, PM10 and PM2.5 per 24 hours at the location still meet the ambient air quality standards set by the government. TSP in the Boiler Area (U1) is in the blue (medium) category, while other measurement locations for TSP, PM10 and PM2.5 at both times are still in the green (good) ISPU category